Korean In-service Teachers’ Perspectives on AI Integration in the Revised English Curriculum - Kim, Rakhun (Secondary English Education, 2024)
This study explores Korean in-service English teachers’ perspectives on the integration of artificial intelligence (AI) technologies into the 2022 Revised Korean National Curriculum for secondary English education. Semi-structured interviews were conducted with ten in-service English teachers from Seoul and Gyeonggi Province to examine their views on the curriculum’s pedagogical objectives, instructional methodologies, and assessment practices incorporating AI technologies. The findings reveal three key insights. First, in terms of pedagogical objectives, teachers highlighted challenges in meeting the high-level learning goals set by the revised curriculum. They emphasized the importance of promoting sentence-level language production beyond rote memorization, but noted the limitations of current AI tools in developing the language creation capabilities. Second, with respect to instructional methodologies, teachers identified significant barriers, including a lack of clear implementation guidelines, issues with technological reliability, and inadequate professional training. Finally, regarding assessment practices, teachers expressed concerns about their reliability and ethical guidelines in using AI technologies, particularly in evaluating productive language skills. These findings highlight the need for comprehensive teacher training programs, robust technological infrastructure, and instructional approaches that effectively integrate AI methodologies while maintaining the strengths of traditional English teaching practices. KCI Citation Count: 0